Effects of estradiol or an estradiol-trenbolone acetate reimplant scheme and time on feed on performance and carcass traits of finishing steers - Robert T. Brandt Jr.; Michael E. Dikeman; Sally L. Stroda (Kansas Agricultural Experiment Station Research Reports, 1992)
Two hundred eighty-eight predominantly British and British crossbred steers (702 lb) were used in a 2x3 factorially arranged experiment. Main effect factors were reimplant scheme [estradiol (E2) vs estradiol plus trenbolone acetate (E2 + TBA)] and time on feed (111, 125 or 139 days). The initial slaughter occurred when 65 to 70% of all steers were estimated to grade low Choice. No interactions occurred for any variable measured. Reimplanting 57 days after the initial implant with E2 + TBA increased overall daily gain 6.9% (P<.003) and feed efficiency 4.9% (P<.005). Feeding steers for an additional 14 or 28 days resulted in linear decreases in overall daily gain (P<.005) and feed efficiency (P<.0004). Reimplanting with E2 + TBA increased (P<.001) carcass weight but did not reduce marbling score or percent Choice carcasses. Feeding steers for an additional 14 or 28 days resulted in linear increases (P<.0001) in hot carcass weight, ribeye area, adjusted backfat (P<.004), and skeletal maturity (P<.0005). Additional days on feed increased dressing percentage (P<.002) and marbling score (P<.05) curvilinearly and tended (P=.25) to increase the percentage of carcasses grading Choice and Prime. Incidence of dark cutters was higher (P<.05) for E2 + TBA carcasses, and was very high at the first slaughter date (54 days after reimplantation). Although feeding for an additional 14 or 28 days can result in heavier live and carcass weights, higher dressing percentage, and increased marbling, poor efficiency of gain may create negative feeding margins.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Estradiol; Trenbolone acetate; Reimplantation; Time on Feed